Conduction-Natural Convection in a Partitioned Triangular Enclosure Filled with Fluid Saturated Porous Media - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Loan (Begell House Inc, 2009)
Numerical analysis has been performed to examine the conduction-natural convection in a partitioned triangular enclosure filled with a fluid-saturated porous medium. The enclosure is heated from the vertical wall and cooled from the inclined wall, while the bottom wall is adiabatic. In addition, the enclosure has a solid partition with finite thermal conductivity and thickness. The finite difference method is used to solve the governing partial differential equations which are written using the Darcy flow model. The parameters which affect heat transfer, flow field, and temperature distribution are the Rayleigh number thickness of the partition, location of the center of the partition, and the thermal conductivity ratio. It is found that heat transfer is an increasing function of the Rayleigh number and thermal conductivity ratio and a decreasing function of partition thickness and partition location at the heated vertical wall.
Keywords: Wall Heat-Conduction; Flow; Cavity